Optimizing the tool life of a hybrid material using genetic algorithm. (2018) - Chanakya Chervith, P.S.M.; Abhilash, P.; Chandrasekhar, A.
Abstract: Manufacturing sector considered as the backbone for economic development of any nation. For competing in the global market and registering high growth we need to concentrate on optimal methods of manufacturing. As the cost of Material is occupying a 70 – 80 % of the total cost and with increasing manufacturing costs and decreasing the profit margins, it is more important for the manufacturers to choose right type of tooling that will produce accurate and precision parts every time at lower costs. The present paper will focus on the hybrid materials, PW30 and GW15, as a tool and various parameters which will affect the tool life. Various parameters that will be considered in this paper are cutting speed, depth of cut and feed rate. The process parameters of different hybrid materials are optimized using Genetic algorithm (GA).